Regulation of Malate Oxidation in Isolated Mung Bean Mitochondria: I. Effects of Oxaloacetate, Pyruvate, and Thiamine Pyrophosphate - Bowman, Emma J. (1976)
In order to investigate the relationship between malate oxidation and subsequent cycle reactions, the effects of oxaloacetate, pyruvate, and thiamine pyrophosphate on malate oxidation in mung bean (Phaseolus aureus var. Jumbo) hypocotyl mitochondria were quantitatively examined. Malate oxidation was optimally stimulated by addition of pyruvate and thiamine pyrophosphate, whose addition lowered the apparent Km for malate from 5 mm to 0.1 mm. Intermediate analysis showed that the stimulatory effect was correlated with removal of oxaloacetate to citrate. Oxaloacetate added alone was shown not to be metabolized until addition of pyruvate and thiamine pyrophosphate; then oxaloacetate was converted in part to pyruvate and also to citrate. These results establish that malate oxidation in mung bean mitochondria is subject to control by oxaloacetate levels, which are primarily determined by the resultant of the activities of malate dehydrogenase, citrate synthase, and pyruvate dehydrogenase.